2009
DOI: 10.1603/029.102.0316
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Role of Olfaction in Host Plant Detection of <I>Scaphoideus titanus</I> (Hemiptera: Cicadellidae) Nymphs

Abstract: The American grapevine leafhopper, Scaphoideus titanus Ball (Hemiptera: Cicadellidae), is the vector of the phytoplasma that causes Flavescence dorée, one of the most threatening grapevine yellows disease. The role of olfaction in host plant detection of this species is still unknown. In this study, the attractiveness of a host plant, the grapevine rootstock Vitis riparia x rupestris 101/14, to nymphs was verified through behavioral bioassays in a vertical glass Y-olfactometer. Furthermore, the olfactory sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Response of D. suzukii to host fruits. The response of mated D. suzukii females to host fruit volatiles was investigated using a dual-choice Y-tube olfactometer (stem 30 cm; arm length 20 cm; arm angle 60 ∘ ; internal diameter 4 cm) (Mazzoni et al, 2009). Each arm of Y-tube was connected to a Pyrex glass bulb (250 mL): one holding the test material (25 g of fresh fruits) and the other serving as the control.…”
Section: Y-tube Olfactometer Bioassaysmentioning
confidence: 99%
“…Response of D. suzukii to host fruits. The response of mated D. suzukii females to host fruit volatiles was investigated using a dual-choice Y-tube olfactometer (stem 30 cm; arm length 20 cm; arm angle 60 ∘ ; internal diameter 4 cm) (Mazzoni et al, 2009). Each arm of Y-tube was connected to a Pyrex glass bulb (250 mL): one holding the test material (25 g of fresh fruits) and the other serving as the control.…”
Section: Y-tube Olfactometer Bioassaysmentioning
confidence: 99%
“…Mechanoreception is the most universal sensory mechanism involved in the various behaviors of insects. The insect mechanoreception or mechanoreceptors has been summarised by French (1988), Keil (1997), McIver (1975; 1985). Mechanoreceptors involve the interoceptors, exteroceptors, and proprioceptors with the latter two groups including hair‐like or trichoid sensilla, campaniform sensilla and the scolopidial or chordotonal sensilla.…”
Section: Discussionmentioning
confidence: 99%
“…Within Homoptera, the Auchenorrhyncha was thought much less responsive to odors than the Sternorrhyncha during intraspecific communication and host‐finding (Todd et al, 1990) but were always emphasized on their acoustical signals for mating. A relatively few species of Auchenorrhyncha have been shown to respond to plant volatiles during host finding (Khan et al, 1988; Klein et al, 1988; Mazzoni et al, 2009; Obata et al, 1981; 1983; Patt and Sétamou, 2007; Saxena and Saxena, 1974; Todd et al, 1990). In Cicadoidea, Magicicada cassini (Fisher) (Klein et al, 1988) had been shown to possess antennal olfactory receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The colored sticky trap is one component of integrated pest management (Hoddle et al, 2002;Rodriguez-Saona et al, 2012). Colors can be recognized by herbivores as visual signals in host location and oviposition (Mazzoni et al, 2009;Fred & Brommer, 2010;K€ uhnle & M€ uller, 2011). The colors attractive to insects are affected by many ecological factors and are generally species-specific (Gaertner & Towner, 1995;Rodriguez-Saona et al, 2012).…”
Section: Introductionmentioning
confidence: 99%